The role of neutrophil to lymphocyte ratio in patients with pTa non-muscle invasive bladder cancer - Mártha Orsolya; Balan Daniel; Porav-Hodade Daniel; Drágus Emőke; Vartolomei Mihai Dorin; Chibelean Călin Bogdan; Borda Angela; Pytel Ákos; Vida Olivér Árpád (Romanian Journal of Laboratory Medicine, 2020)
Introduction: The peritumoral inflammatory reaction has a substantial importance in the oncologic outcome of bladder cancer (BC). One biomarker proven to be practical and accessible is the NLR (neutrophil-to-lymphocyte ratio) for high risk non-muscle invasive bladder cancer (NMIBC). The aim of the study was to investigate the role of NLR as a prognostic biomarker for disease recurrence, progression and survival of p Ta (pathological assesment of the primary tumor) NMIBC.